Microsoft FrontPage 2000 step by step - Palmer, Scott (Redmond, Washington : Microsoft Press, 1999)
MICROSOFT FRONTPAGE 2000 STEP BY STEP is the easiest and fastest way to teach yourself to use the latest version of Microsoft s powerful Web page design program. Work through every lesson to complete the full course, or do individual lessons to learn just the skills you need. Either way, you learn at your optimum pace from the teacher who knows you best you. With this book and Microsoft FrontPage 2000, you ll learn to: Design and create a Web site understand the Web; build a Web site; create a home page; link Web pages; manage a Web site Format and enhance Web pages add style with FrontPage themes and components; create lists and tables; add multimedia images, sound, video, and animations; use HTML style sheets Use advanced Web site techniques create forms for user feedback; create a frames page or a no-frames page; use shared borders and navigation bars Publish and update your Web site test your Web site; verify and update hyperlinks; publish to a Web server; manually upload Web files; get reports; manage FrontPage tasks; create a company intranet.
Includes index.
Keywords: Web sites -- Design; Web publishing; Microsoft FrontPage